Electroacupuncture Preconditioning Reduces Oxidative Stress in the Acute Phase of Cerebral Ischemia-Reperfusion in Rats by Regulating Iron Metabolism Pathways - Runyu Liang (Hindawi Limited, 2021)
Background. Oxidative stress is an important mechanism of cerebral ischemia-reperfusion injury. Ferroptosis caused by iron overload after cerebral ischemia-reperfusion is considered a common cause of oxidative stress. Many recent studies have shown that electroacupuncture (EA) can regulate the expression of inflammatory factors, and the use of electroacupuncture preconditioning can produce a protective effect, which can reduce injury after cerebral ischemia and reperfusion. We aimed to assess whether EA could be used to reduce oxidative stress. Methods. The oxidative stress level of rats during the acute phase of cerebral ischemia and reperfusion was assessed with and without preconditioning with EA. Molecular biology methods were used to detect iron metabolism and oxidative stress-related proteins. Results. Rats that had EA preconditioning had lower infarct volumes than rats in the control group. Furthermore, western blot analysis showed that the expression of iron metabolism-related protein FPN-1 was higher in the intervention group than in the model group after reperfusion. In this regard, further investigation also demonstrated higher expression of glutathione and glutathione peroxidase-4, and lower reactive oxygen species values in the brain tissue of the EA group were compared with those of the control group rats. Conclusions. Electroacupuncture preconditioning can reduce oxidative stress after cerebral ischemia-reperfusion by regulating iron overload.